2011
DOI: 10.1186/1471-2407-11-130
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators in breast cancer: Coordinated expression of TNFα & IL-1β with CCL2 & CCL5 and effects on epithelial-to-mesenchymal transition

Abstract: BackgroundThe inflammatory chemokines CCL2 (MCP-1) & CCL5 (RANTES) and the inflammatory cytokines TNFα & IL-1β were shown to contribute to breast cancer development and metastasis. In this study, we wished to determine whether there are associations between these factors along stages of breast cancer progression, and to identify the possible implications of these factors to disease course.MethodsThe expression of CCL2, CCL5, TNFα and IL-1β was determined by immunohistochemistry in patients diagnosed with: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
220
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(238 citation statements)
references
References 74 publications
15
220
0
3
Order By: Relevance
“…All these cytokines have been implicated in breast cancer progression previously. [46][47][48] To test the effect of these cytokines on PKCl/i activation, we treated MDA-MB-231 cells with different cytokines and tested phosphorylation of PKCl/i. Intriguingly, we found that both TGFb1 and IL1b, individually and in combination, induced PKCl/i phosphorylation in MDA-MB-231 cells (Figure 6a and Supplementary Figure S8a).…”
Section: Resultsmentioning
confidence: 99%
“…All these cytokines have been implicated in breast cancer progression previously. [46][47][48] To test the effect of these cytokines on PKCl/i activation, we treated MDA-MB-231 cells with different cytokines and tested phosphorylation of PKCl/i. Intriguingly, we found that both TGFb1 and IL1b, individually and in combination, induced PKCl/i phosphorylation in MDA-MB-231 cells (Figure 6a and Supplementary Figure S8a).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, from the coculture of EC and MC versus simultaneously MC alone and EC alone, 17 genes from the 27 known differentially expressed genes were linked to migratory and/or embryonic/cancer stem cell properties: nine overexpressed genes: CCL2, ICAM1, SELE, IL6, TRAF1, SERPINB2, CXCL6, PDGFB and EVX1, and eight underexpressed genes: CFDP1, BLID, RGNEF, MALT1, RANBP9, UPF1, PLAA and ZXDC. More specifically, these genes have demonstrated properties linked to (i) cancer cell migration: CCL2 [26,27], ICAM1 [28], IL6 [29], RGNEF [30] and RANBP9 [31]; (ii) cancer progression and metastasis: CCL2 [26,27,32], ICAM1 [33,34], SELE [35,36], TRAF1 [37], IL6 [29], SERPINB2 [38], CXCL6 [39], BLID [40], MALT1 [41], UPF1 [42], PLAA [43], RGNEF [44], ZXDC [45]; (iii) EMT: CCL2 [46] and IL6 [29] ; and (iv) embryonic and/or cancer stem cell properties: CCL2 [46][47][48] , PDGFB [49] , EVX1 [50], CFDP1 [51] and RANBP9 [52] . Furthermore, the 15 most significantly enriched functional groups analyzed by IPA included: development, cell movement, cancer, and embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CCL2 and CCL5 in the IDC-with-relapse group was associated with further elevated expression of IL1b and TNF-a. 35 In human breast tumor cells, CCL5-containing vesicles on microtubules traffic from the endoplasmic reticulum to the post-Golgi stage before CCL5 is released, and this process is controlled by the stiffness of the actin cytoskeleton in a manner dependent on the (43)TRKN(46) sequence of the 40 s loop of CCL5.…”
Section: Ccl5 and Human Breast Cancer (Bc)mentioning
confidence: 99%